Study on End-wall Slope Stability of Surface Coal Mine under the Condition of Combined Open-pit Mining with Underground Mining - Peng Hongge; Cai Qingxiang; Zhou Wei; Shu Jisen (Institute of Advanced Engineering and Science, 2016)
With the deepening of surface coal mine, the application of combined surface mining with underground mining is increased now. According to the influence analysis of underground mining on surface coal mine end-wall slope, the thin plate model of mined slope was proposed with distortion and stress distribution of the girder studied. Considering the practice of combined surface mining with underground mining, the modified method was put forward. Based on the roof breaking law of mined slope, the minimum width of protecting coal pillar was elicited. Subsequently this paper took the combined mining practice of Anjialing surface mine as example to study the subsidence law of roof and the influence of underground mining to surface mine slope. The research conclusion indicates that under the condition of combined mining the deformation and subsidence of overlying strata are obvious with a clear lag time, and the ceiling distortion evokes distortion of mined slope, which can be used as the theory sustainment to stabilization of mined slope under combined surface mining with underground mining.